Water quality changes in a short-rotation woody crop riparian buffer. (December 2017) - Rosa, David J.; Clausen, John C.; Kuzovkina, Yulia
Abstract: Converting riparian buffers in agricultural areas from annual row crops to short rotation woody crops (SRWCs) grown for biofuel can provide both water quality benefits and a financial incentive for buffer adoption among agricultural producers. A randomized complete block design was used to determine water quality changes resulting from converting plots previously cultivated in corn to SRWC willow ( Salix . spp ) adjacent to a stream in Storrs, CT. Both overland flow and ground water samples were analyzed for total nitrogen (TN) and total phosphorus (TP). Additionally, overland flow was analyzed for suspended solids concentration (SSC) and ground water samples were analyzed for nitrate + nitrite (NO2 +NO3 -N). Lower (p = 0.05) concentrations of TN (41%) and TP (53%) were observed in overland flow from willow plots than from corn plots. Shallow ground water concentrations at the edge of willow plots were lower in TN (56%) and NO3 +NO2 -N (64%), but 35% higher in TP, than at the edge of corn plots. SSC was also lower (71%) in overland flow associated with willow compared to corn. The treatment had no effect on the depth or volume of overland flow or mass export. The changes in concentrations resulting from conversion of corn to SRWC in a riparian buffer are similar to those observed in restored and established buffers. Highlights: A riparian area cultivated in corn was converted to a SRWC of willow for biofuel. Conversion reduced concentrations of N, P and suspended solids in overland flow. Conversion reduced N in ground water, but increased P. A SRWC has water quality benefits similar to other buffer management approaches.